(untitled) (Brazilian Journal of Radiation Sciences (BJRS), 2021)
In the end of operational life, a nuclear power plant should be decommissioned to release its site for a new purpose. The decommissioning cost estimation is part of the decommissioning plan, which also include the decommissioning strategy definition. The cost estimation is performed by management tools, most of them according the bottom-up approach. However, this approach usually requires large quantities of data and detailed knowledge of the site conditions and the project phases, which are often unknown in the project beginning, requiring the adoption of several assumptions. Otherwise, the top-down approach requires less data or assumptions, and the project details is known as it became mature. Due to this, the top-down approach is a better approach for cost estimation during planning phase than the bottom-up. Despite it, most part of management tools found in literature to cost estimation are structured according the bottom-up approach. To suppress this lack, recently a new management tool was developed according the top-down approach, being able to estimate the decommissioning cost of nuclear power plants for budget/bid purposes. This work aims to present the cost estimation to decommissioning a multiple reactor power site with similar characteristics of the Brazilian ones, which would be used as benchmark. The results demonstrated that the interdependencies among the plants are important and affects significantly the cost to decommissioning each plant. This work is part of a research that is under course in which several strategies alternatives would be evaluated.